DISSEMINATING MULTICULTURALISM THROUGH THE TEACHING OF TRANSLATION - Laksono, Arido (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT Students are expected to change the world. Their perspectives represent the way they view the world and its phenomena. The broader knowledge they possess, the more tolerance they have in interpreting life. In the global era, students should understand the importance of having good knowledge in multiculturalism. They will involve in an inter-cultural encounter since sources of information are widely offered. The willingness to have such an open mind is required in order to develop a better place to live and work. One way to disseminate multiculturalism values is using text containing information about culture and social values. The text written in English or Bahasa Indonesia for the class designed in disseminating multiculturalism is Translation. Here, students are taught to interpret the messages conveyed and translate the information from the source language to the target language correctly. Teacher must have good and creative technique in delivering the material so that students really enjoy the class and deeply understand the topic. The teaching and learning process in Translation class, therefore, is an effective medium to achieve the expected purpose as stated above. Theory of translation will not be the one and only theory to do the translation job, but it also needs comprehensive knowledge on other social sciences. Hence, translation class will not only discuss lines of words in a paragraph, but also reciprocal discussion among the members of the class. At the end, students will have the ability to translate such information in a text correctly and to establish civic society with more open comprehension over society and its culture. Keywords: theory of translation, multiculturalism, teaching-learning process, globalization.